VoIP Network and Protocols in IoT Applications - Remigiusz RAJEWSKI; Marek WOJTASIK (Communications of International Proceedings, 2025)
This paper presents the application of VoIP technology in the Internet of Things (IoT) environment, with particular emphasis on the integration possibilities of both technologies. The potential of using Raspberry Pi as a VoIP server and as a control hub for smart offices and homes is discussed, highlighting its low cost, efficiency, and flexibility. Key protocols such as SIP, RTP, and SDP, which enable effective voice and signaling communication in IP networks, were used. Various server environments are compared, identifying Asterisk as the most optimal solution for small and medium VoIP installations integrated with IoT, as opposed to alternatives such as FreeSwitch or 3CX, which may require more resources. In addition, the implementation of passive devices based on ESP32 microcontrollers is described, which enable functions such as alerting, remote device control, and collecting and processing sensor data. Practical applications in smart home and office environments, such as process optimization, increased security, and the ability to remotely manage systems, are highlighted. The results of the study confirm that the combination of VoIP and IoT technologies can significantly improve automation and communication in smart systems, while minimizing implementation costs and allowing further development toward more advanced solutions.
Keywords: IoT sensors; VoIP; microcontroller ESP32